Coronavirus Persistence on a Plastic Carrier Under Refrigeration Conditions and Its Reduction Using Wet Wiping Technique, with Respect to Food Safety - Malenovská, Hana (Food and environmental virology, 2020)
The global SARS-CoV-2 pandemic dictates that anti-contagion strategies should become matters of essential routine in everyday life. Fomite transference is one of the routes of transmission that has been considered for this virus. However, the risks associated with contaminated surfaces of food packaging kept in refrigerators have not yet been adequately assessed. In this study, a surrogate virus, Alphacoronavirus 1, was used to investigate the persistence of coronavirus dried on a plastic carrier at 4 °C. Techniques of wet wiping, with or without disinfectant saturation, were employed to evaluate their effectiveness in the elimination of the virus. If not wiped, the loss of infectivity of the virus on plastic surfaces was, on average, 0.93 log10 (i.e. 83%) per day of storage at 4 °C. Wiping with water-saturated material reduced the initial virus titre on the plastic carrier by 2.4 log10 (99.6%); the same results were achieved through wiping with bactericidal wipes containing ethanol. Wipes saturated with a combination of disinfectant agents (didecyl-dimethyl-ammonium chloride, hydrogen peroxide) decreased the virus titre still more efficiently, by 3.8 log10 (99.98%) and also significantly prevented further transfer of the virus to a secondary surface through wiping. Thus SARS-CoV-2 transmission potential via contaminated plastic packaging and food may be efficiently eliminated by wet-wiping, especially when wipes saturated with specific disinfectants are used.
Keywords: Disinfectants; Hydrogen Peroxide; Coronavirus Infections; Virus survival; fomity; Fomites; Plastics; SARS-CoV-2; Covid-19; ethanol; Disinfection; dezinficiencia; Alphacoronavirus 1; Quaternary Ammonium Compounds; Food safety; skladování potravin; obaly potravin; lidé; peroxid vodíku; Food Safety; Anti-Bacterial Agents; Food Storage; Coronavirus; chlazení; kvartérní amoniové sloučeniny; koronavirové infekce; COVID-19; plastické hmoty; Pneumonia, Viral; Ethanol; Betacoronavirus; virová pneumonie; pandemie; voda; dezinfekce; Water; Refrigeration; Food Packaging; bezpečnost potravin; Refrigerated food; antibakteriální látky; Surface contamination; Pandemics; Humans